Analisis Kemampuan Matematika Siswa SMAS Manda Elu dalam Menyelesaikan Soal pada Materi Perbandingan Trigonometri untuk Siswa Kelas X - Lede, Yulius Keremata; Moza, Florida; Zogara, Leonard (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to determine the Mathematics ability of SMAS Manda Elu Students in solving Problems on Trigonometric Comparison Material for Grade X Students. The research method is a survey method. The subjects of the study were 28 grade X SMAS Manda Elu students and 3 students were selected based on the same answer category to be confirmed through interviews. Data collection techniques in this study were documentation and interviews. The research instrument was a test question taken from the trigonometric comparison material and interview guidelines related to problem-solving skills. This data was analyzed using three types, namely Data Reduction, and making conclusions. Students are not familiar with Polya's steps, none of them write from what is known and asked, let alone looking back because they are not used to it. Students also usually write formulas directly and determine the final result or answer to the question. So the results of this study found that not even 50% of students' ability to solve trigonometric comparison problems through Polya's steps.